Vloga šole pri jezikovnem načrtovanju - Bergoč, Simona (Šolsko polje, 2006)
The paper considers the Slovene Language Curriculum in Grammar Schools (gimnazija) that came into force in 1998. Analyzing the proposed concept of language education, it focuses on four issues: the relationship between language and culture, the relationship between language and ethnic identity, the hierarchal status of languages and critical language awareness. The paper demonstrates that the established curriculum disagrees with the socio-linguistic condition of multi-cultural society by reproducing homogeneism as a value promoted by nation-states on one hand and on the other by mirroring the collective minority frame of mind which still pervades a certain direction in language planning and was caused by the underprivileged status of Slovene language in certain fields of its use in the context of multi-national Yugoslavia.
Keywords: sociolinguistics; sociolingvistika; jezikovna vzgoja; učni načrti; curriculum; kurikulum; Slovene; slovenščina; gimnazije